2017
DOI: 10.1007/s00037-017-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on holographic algorithms

Abstract: Abstract. We define the notion of diversity for families of finite functions, and express the limitations of a simple class of holographic algorithms in terms of limitations on diversity. We go on to describe polynomial time holographic algorithms for computing the parity of the following quantities for degree three planar undirected graphs: the number of 3-colorings up to permutation of colors, the number of connected vertex covers, and the number of induced forests or feedback vertex sets. In each case the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This result gives a way forward for the development of the structural theory of holographic algorithms on higher domain sizes in the same vein as Cai et al's work on domain size 2. In [24], Valiant gave examples of holographic algorithms on domain size 3, but holographic algorithms on higher domain sizes have yet to be explored. Our result shows that for domain size k, we can focus on understanding changes of basis in M 2 log 2 k ×k (C) rather than over an infinite set of dimensions, just as the collapse theorem of Cai and Lu [8] showed that on the Boolean domain, they could focus on understanding changes of basis in GL 2 (C).…”
Section: Our Results and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This result gives a way forward for the development of the structural theory of holographic algorithms on higher domain sizes in the same vein as Cai et al's work on domain size 2. In [24], Valiant gave examples of holographic algorithms on domain size 3, but holographic algorithms on higher domain sizes have yet to be explored. Our result shows that for domain size k, we can focus on understanding changes of basis in M 2 log 2 k ×k (C) rather than over an infinite set of dimensions, just as the collapse theorem of Cai and Lu [8] showed that on the Boolean domain, they could focus on understanding changes of basis in GL 2 (C).…”
Section: Our Results and Techniquesmentioning
confidence: 99%
“…In his new framework, multiple strands of computation get combined in a "holographic" mixture with exponential, custom-built cancellations specified by a choice of basis vectors to produce the final answer. With this change-of-basis approach, Valiant [21,22,23,24] found polynomial-time solutions to a number of counting problems, minor variants of which are known to be intractable, and noted that the only criterion for their existence was the solvability of certain finite systems of polynomial equations. As a notable example, whereas counting the number of satisfying assignments to planar, read-twice, monotone 3-CNFs is #P-complete and even the same problem modulo 2 is NP-hard under randomized reductions, the same problem modulo 7, known as # 7 Pl-Rtw-Mon-3CNF, has a polynomial-time holographic solution [21].…”
Section: Introduction 1matchgates and Holographic Algorithmsmentioning
confidence: 99%
“…But for #CSP over higher domains, the situation is different. Over the general domain of size q ≥ 3, there are only a few holographic algorithms with matchgates [27,1]. But it can be argued that they are problems that actually get transformed to a Boolean domain #CSP problems.…”
Section: For Any Finite Set Of Constraint Functions F Over Boolean mentioning
confidence: 99%
“…The possibility that accidental or freak objects in the enumeration exist cannot be discounted if the objects in the enumeration have not been studied systematically." Indeed, if any "freak" object exists in this framework, it would collapse #P to P. Therefore, over the past 10 to 15 years, this technique has been intensely studied in order to gain a systematic understanding of the limit of the trio of holographic reductions, matchgates, and the FKT algorithm [6,7,15,16,32,37,38,42,46]. Without settling the P versus #P question, the best hope is to achieve a complexity classification.…”
Section: Introductionmentioning
confidence: 99%